2015
DOI: 10.1111/vsu.12348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intramedullary Rod Diameter on a String of Pearls Plate‐Rod Construct in Mediolateral Bending: An In Vitro Mechanical Study

Abstract: Biological osteosynthesis often relies on more compliant bridging constructs to promote beneficial micromotion at the fracture. Our study suggests use of a smaller diameter IMR (SOP-32) is comparable to a conventional plate-rod construct (LC-DCP-40). Should greater compliance be desired, an even smaller diameter IMR (SOP-24) may prove beneficial while as stable as an accepted bicortical construct (SOP-B).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Without any data for clinical comparison, this study concluded that small diameter IM pin may prove beneficial in clinical cases where a locking SOP-rod construct is used. 60 That study also supported the use of monocortical screws in locking plate-rod constructs. Despite finding significant differences in deformation and compliance between mono and bicortical SOP fixation without a pin, these differences were eliminated by adding a 24% IM pin to the monocortical SOP constructs.…”
Section: (C) Locking Plate-rod Studiessupporting
confidence: 58%
“…Without any data for clinical comparison, this study concluded that small diameter IM pin may prove beneficial in clinical cases where a locking SOP-rod construct is used. 60 That study also supported the use of monocortical screws in locking plate-rod constructs. Despite finding significant differences in deformation and compliance between mono and bicortical SOP fixation without a pin, these differences were eliminated by adding a 24% IM pin to the monocortical SOP constructs.…”
Section: (C) Locking Plate-rod Studiessupporting
confidence: 58%
“…17,37,38 If CCP are to be used in tibial fractures that are unable to be reconstructed, supplemental fixation in the form of an intramedullary pin or orthogonal plate may be advisable. 39,40 Further clinical investigation of both plating systems is warranted to determine optimal applications when stabilizing tibial fractures in cats.…”
Section: Discussionmentioning
confidence: 99%
“…A generic femoral bone model was designed by using the morphometric measurements of the native feline femurs obtained in the first phase of the study. The overall shape of this symmetrical model was similar to that of a canine bone model previously used in our laboratory . The model featured a 20‐mm outer diameter segment used for linkage to custom holding fixtures at each extremity.…”
Section: Methodsmentioning
confidence: 99%